PERANCANGAN ILUSTRASI RUMAH BERTEMA “NURSE” UNTUK KARAKTER OCTALAND IP DI OCTAGON STUDIO BANDUNG - Muhamad Nizar Al Muizzy; Maria Saraswati Bijakbestari (Universitas Trisakti, 2023)
Learning media using technology is currently very influential in the world of education. With the development of technology, education is easy to obtain. Technology media in the form of 3D illustrations, makes it easier for children aged 4-6 years to understand the lessons. Octaland is an exploratory IP aimed primarily at children who want to get to know the types of work that exist with an interesting illustrative approach. The making illustrations of Nadia’s house is made using objects that are correlated with the medical world to make it easier for children to get to know Nadia as a nurse. The process of making this house illustration with the theme of a nurse is made using a simple and easy-to-recognize illustration. The selection of shapes that tend to be oval and curved lines are deliberately used because the target market is children and also represents Nadia’s gentle character.Keyword: 3D illustrations, Octaland IP characters